Media Gambar untuk Meningkatkan Perbendaharaan Kata pada Siswa TK B Bahrul Ulum Lamongan - Titin Faridatun Nisa'; Kholiyun Lutfiyah (Universitas Trunojoyo Madura, 2014)
Improving the quality of learning should be implemented in an integrated, systematic, and continuous. One way is through the medium of drawing. Media images provide the understanding, learning and mastery of language skills. The purpose of this study was to describe the extent to which the use of media images can improve the students’ vocabulary TK B Bahrul Ulum Lamongan. This research is a class act with two cycles. The initial condition (pre-action) showed that students who self 0 %, capable of without the help of teachers by 10 %, was able to help a great teacher of 10 %, was able to help a great teacher of 10 %, was able to help teachers 65 % and 25% can not afford. In cycle I, the results obtained are independent students 10 %, capable of without the help of teachers by 20 %, was able to help teachers 70 % and that is not capable of 0 %. While on cycle II, the results obtained are independent student 30 %, capable of without the help of teachers by 50 % able to help teachers 20 % and not capable of 0 %. This suggests that an increase in students’ vocabulary TK B Bahrul Ulum Lamongan using media images.